PERKAWINAN LINTAS AGAMA DAN PENGARUHNYA TERHADAP KEHIDUPAN RUMAH TANGGA (SEBUAH KAJIAN TAFSIR) - Much. Muallim (IAIN Ambon, 2017)
Marriage is social action that has biological nuanced, but it become attention, even the part of Islamic teachings .This is evidenced by many verses of the Qur'an and Hadith (narrations) of the prophet Muhammad that explain about the marriage. He (the prophet) gives guidance and concrete examples on the subject, which of course (all of them) to exemplify the procedures and rules that should be followed by Muslims. But some problems will appear, when the marriage is confronted with interreligious cases; among the perpetrators, which it has reaped a long debate since early time of interpreting holy Quran by the first generation of Muslims (read: Companions). The debate continues, even now. In the formative period of Quranic interpretation, the debate appeared among Islamic scholars about feasibility of Muslims to marry ahl al-kitab women. In this case, majority of companions including 'Umar bin Khatthab ra, Uthman ibn' Affan ra, 'Ali bin Abi Talib ra, and also Ibn' Abbas allowed the marriage (between Muslim men and ahl al-kitab women), although there are several requirements that must be met. But according to 'Abdullah bin ‘Umar, the marriage should not happen, because the abuses that committed by ahl al-kitab has reached the stage of shirk, associating partners with Allah. Nevertheless, the next generation (tabi'i), more likely to take the first opinion (majority opinion), because it was considered more suitable with the practice of zahir al-nass. Thus, conceptually, inter-religious marriages between Muslim men with ahl al-kitab women can be done. But in practice, its implementation must consider several important aspects, which relate to due to marriage, both juridical-normative and social view. Among some urgent things to be caution is about the religious future of their children, as well as accountability (Muslim man) as the head of the family, in the Hereafter. And if each potential perpetrators of interfaith marriage actually consider some of these results, they won’t certainly be easy to do the interfaith marriage. Keywords: interfaith marriage and Quranic interpretation